Making Liquid Organic Fertilizer: Community Empowerment Sranak village, Trucuk sub-district, Bojonegoro district - Nihayah, Hamidatun; Kartini, Alif Yuanita; Fithriyah, Dewi Niswatul; Sufiandi, Enrico; Ningtiyas, Putri Ayu (Universitas Islam Nahdlatul Ulama Jepara, 2025)
The majority of the people in Sranak village Trucuk, Bojonegoro district, make their living as farmers. But what is experienced is that the harvest is not proportional to the expenses used for maintenance costs. In fact, the maintenance costs are greater than the harvest. This is because some fertilizer prices are very expensive and fertilizer subsidies from the government are also limited. An economical solution is to replace subsidized fertilizers from the government with organic fertilizers through the use of natural ingredients. The purpose of this community service activity is as a form of community empowerment through the manufacture of organic liquid fertilizer from natural ingredients that are easily obtained and will be able to replace chemical fertilizers and subsidized fertilizers from the government. The method applied in this community service activity is a training method that begins with a Focus Group Discussion followed by determining the material, implementation to evaluation. The community of Sranak village 75% successfully understood the material received and could add to their agricultural yields and minimize the use of chemical fertilizers after applying liquid organic fertilizer. The application of this simple technology can be a pilot in other villages in creating economic and environmental sustainability.